Association of Autofluorescence-Based Detection of the Parathyroid Glands During Total Thyroidectomy With Postoperative Hypocalcemia Risk: Results of the PARAFLUO Multicenter Randomized Clinical Trial - Benmiloud, Fares (JAMA Surg, 2019)
IMPORTANCE: Because inadvertent damage of parathyroid glands can lead to postoperative hypocalcemia, their identification and preservation, which can be challenging, are pivotal during total thyroidectomy. OBJECTIVE: To determine if intraoperative imaging systems using near-infrared autofluorescence (NIRAF) light to identify parathyroid glands could improve parathyroid preservation and reduce postoperative hypocalcemia. DESIGN, SETTING, AND PARTICIPANTS: This randomized clinical trial was conducted from September 2016 to October 2018, with a 6-month follow-up at 3 referral hospitals in France. Adult patients who met eligibility criteria and underwent total thyroidectomy were randomized. The exclusion criteria were preexisting parathyroid diseases. INTERVENTIONS: Use of intraoperative NIRAF imaging system during total thyroidectomy. MAIN OUTCOMES AND MEASURES: The primary outcome was the rate of postoperative hypocalcemia (a corrected calcium <8.0 mg/dL [to convert to mmol/L, multiply by 0.25] at postoperative day 1 or 2). The main secondary outcomes were the rates of parathyroid gland autotransplantation and inadvertent parathyroid gland resection. RESULTS: A total of 245 of 529 eligible patients underwent randomization. Overall, 241 patients were analyzed for the primary outcome (mean [SD] age, 53.6 [13.6] years; 191 women [79.3%]): 121 who underwent NIRAF-assisted thyroidectomy and 120 who underwent conventional thyroidectomy (control group). The temporary postoperative hypocalcemia rate was 9.1% (11 of 121 patients) in the NIRAF group and 21.7% (26 of 120 patients) in the control group (between-group difference, 12.6% [95% CI, 5.0%-20.1%]; P = .007). There was no significant difference in permanent hypocalcemia rates (0% in the NIRAF group and 1.6% [2 of 120 patients] in the control group). Multivariate analyses accounting for center and surgeon heterogeneity and adjusting for confounders, found that use of NIRAF reduced the risk of hypocalcemia with an odds ratio of 0.35 (95% CI, 0.15-0.83; P = .02). Analysis of secondary outcomes showed that fewer patients experienced parathyroid autotransplantation in the NIRAF group than in the control group: respectively, 4 patients (3.3% [95% CI, 0.1%-6.6%) vs 16 patients (13.3% [95% CI, 7.3%-19.4%]; P = .009). The number of inadvertently resected parathyroid glands was significantly lower in the NIRAF group than in the control group: 3 patients (2.5% [95% CI, 0.0%-5.2%]) vs 14 patients (11.7% [95% CI, 5.9%-17.4%], respectively; P = .006). CONCLUSIONS AND RELEVANCE: The use of NIRAF for the identification of the parathyroid glands may help improve the early postoperative hypocalcemia rate significantly and increase parathyroid preservation after total thyroidectomy. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT02892253